Review of the BPHTB Collection System in the Transfer of Land and or Building Rights according to Lamongan Regency Regulation No. 10 of 2023 concerning Regional Taxes - Muljono, Bambang Eko; Royani, Ahmad; Sri Widayanti, Nurul Mahmuda (Universitas Islam Lamongan, 2024)
ABSTRACT Land and Building Acquisition Fee (hereinafter abbreviated as BPHTB) according to Law No. 1 of 2022 in Article 1 paragraph (37) states